Organometallics in synthesis : fourth manual - Lipshutz, Bruce H. (Hoboken, New Jersey : John Wiley & Sons, 2013)
"This manual is essential reading for all synthetic organic chemists, providing the most useful reference on organometallics for practicing researchers. The featured elements in this manual are copper, rhodium, nickel, and gold. Background information about the organometallic class, the various methods to prepare compounds, and their use in synthetic reactions are coupled with mechanistic considerations and future research opportunities for each class. Readers will find hands-on, practical, easy-to-follow examples of the preparation of organometallics and their applications in organic synthesis"--
"Offers an essential resource for all synthetic organic chemists, featuring chapters for preparing and utilizing the most important and relevant organometallic compounds in organic synthesis. Organized into chapters by type of organometallic: copper, rhodium, nickel, and gold"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organic compounds -- Synthesis; Organometallic compounds; SCIENCE / Chemistry / Organic; Organic compounds -- Synthesis; Organometallic compounds; Organische Synthese; Metallorganische Verbindungen; Organometaalverbindingen; Synthese (chemie); Electronic books; Handboeken (vorm); Electronic books